2020
DOI: 10.1016/j.sjbs.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Thunbergia laurifolia leaf extract partially recovers lead-induced renotoxicity through modulating the cell signaling pathways

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Pathogenesis and pathophysiology of Pb-induced toxicity have been linked to the production of free radicals that generate oxidative stress and deplete the antioxidant defense system (Nasiruddin et al, 2020;Gadde et al, 2021). According to our research, the birds in the Pb-induced toxicity group showed a noticeably higher level of hydrogen peroxide (H2O2) production, lipid peroxidation product (MDA) content, and oxidative stress in the liver of the experimental birds.…”
Section: Discussionmentioning
confidence: 78%
“…Pathogenesis and pathophysiology of Pb-induced toxicity have been linked to the production of free radicals that generate oxidative stress and deplete the antioxidant defense system (Nasiruddin et al, 2020;Gadde et al, 2021). According to our research, the birds in the Pb-induced toxicity group showed a noticeably higher level of hydrogen peroxide (H2O2) production, lipid peroxidation product (MDA) content, and oxidative stress in the liver of the experimental birds.…”
Section: Discussionmentioning
confidence: 78%
“…Our ndings also con rmed earlier reports on toxicity of NaF on cardiovascular system (Oyagbemi et We observed from our study that NaF intoxication caused signi cant increase in blood urea nitrogen (BUN) and creatinine levels. The increase in BUN and creatinine has been associated with various degrees of renal injuries (Nasiruddin et al 2020;Ni et al 2021). The observed nephrotoxicity by NaF might be due to free radical generation and increase protein catabolism with concomitant systemic oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…could mitigate cadmium (Cd)-induced organ damage in the liver and kidney, blood and urine Cd levels remained unchanged. Similarly, Rana et al [16] reported partial recovery of Cd-damaged kidney organs in rats treated with RC water crude extract. Notably, RC treatment (100 and 200 mg/kg body weight) led to a reduction in the expression of TNF-α, iNOS, and COX-2, all of which are inflammatory cytokines [16].…”
Section: Introductionmentioning
confidence: 87%